Economic Security – New Approaches in the Context of Globalization - Gabriel Andruseac (CES Working Papers, 2015)
Nowadays, more than ever, economic relations between states are the ones that define the general character of the relations between them and establish economic security as a concept which cannot be neglected anymore. Globalization, the process that shapes the international environment, undermines the old definition of economic security and forces its redefinition. The article aims to identify and analyse the effects of globalization on economic security and the new approaches it takes in this context.
Keywords: F52; F59; F60; 330; security; economy; national; globalization; policies